Analysis of Adverse Reactions of Blood Transfusion and Discussion of Influencing Factors in Linyi Area from 2013 To 2020 - Xiuping Zhang; Yanli Zhang; Cao Qi; Chunling Ma (Tehran University of Medical Sciences, 2021)
Background: We aimed to explore the influencing factors of clinical adverse blood transfusion reactions, to provide theoretical basis and support for clinical safe blood transfusion, and to minimize the occurrence of adverse blood transfusion reactions. Methods: The method was to retrospectively analyze the report of adverse blood transfusion reports from 6 hospitals in Linyi area, Shandong, China to the blood station in Linyi City center from 2013 to 2020. We aimed to classify factors, analyze the occurrence of adverse transfusion reactions, and discuss the correlation between the occurrence of adverse transfusion reactions and the above factors. Results: Overall, 248 patients (77.98%) had a history of blood transfusion. The difference between this group and the group with no history was statistically significant (P<0.05). The incidence of adverse transfusion reactions in middle-aged and elderly patients was relatively high, especially for those over 50 yr old, with an adverse reaction of 135, for example, the proportion reached 42.45%. In addition, a retrospective analysis found that the occurrence of adverse transfusion reactions was mostly concentrated from Mar to Sep, a total of 228 cases, accounting for 71.69% of all adverse reactions, which was the highest incidence of adverse transfusion reactions. Conclusion: The main adverse reactions of transfusion were allergic reactions, followed by non-hemolytic febrile reactions, mainly caused by transfusion of suspended red blood cells.